Numerical Modelling of Microcellular Foaming Injection Moulding - J. Nabiałek; T. Jaruga (Archives of Metallurgy and Materials)
The results of computer modelling of an injection moulding process with microcellular foaming (MuCell®) were presented in this work. The process is based on the dissolving nitrogen in a liquid polymer which is possible when nitrogen is in supercritical fluid state (SCF). After pressure drop of the melt in the injection mould the intensive nucleation of pores occurs and, as the result, the material with high concentration of small pores is created. The pores obtained in this way are of much smaller size than in a conventional foaming process. The pore size in the cross-section of an exemplary injection moulded part was calculated in the computer modelling and compared to the results of microscopical investigation made on the real injection moulded part. It was found that the size of the pores depends on the flow length inside the injection mould and on the position in the part’s cross-section.